HONEYCOMB a desktop PC with added visual aids and physical design changes to aid first time PC upgraders - Llanes, John Edward Z. (College of Fine Arts, University of the Philippines Diliman, 2017)
Desktop computers are already standardized and user serviceable for a long time and doing upgrades is more cost effective than buying a new system outright every time. Unfortunately not may people are aware of it and if they do know they may not be comfortable doing it themselves and have someone else do it for them. The goal is to make the internal components of a desktop PC identifiable at a glance so that user is a lot more aware and knowledgeable about the insides of their computer, ideally encouraging them to do it themselves saving time and money as well as gaining knowledge. This system is target towards people who push their computers to the limit like gamers, video editions, CAD software users, 3D rendering users, animators, and any other heavy users, and thus need to upgrade their system more often.